2016
DOI: 10.1007/s12039-016-1159-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of an electrochemical DNA biosensor for detection of specific Mycobacterium tuberculosis sequence based on poly(L-glutamic acid) modified electrode

Abstract: An electrochemical DNA biosensor was developed by avidin-biotin interaction of a biotinylated probe and avidin-attached, poly(L-glutamic) acid coated pencil graphite electrode (PGA/PGE) for detection of specific Mycobacterium tuberculosis DNA sequence. The discrimination of fully complementary hybridization and mismatch hybridization was carried out by electrochemical reduction current of Meldola's Blue (MDB) in square wave voltammetry (SWV). The calibration graph of the DNA biosensor was linear between 1.5-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The same strategy has also been used to detect cardiac troponin I (cTnl) biomarker (C. C. Zhang, Sun, et al, 2020). Furthermore, Yesil et al (2016) reported using poly( l ‐glutamic) acid films coated on the pencil graphite electrode surface to anchor avidin for immobilization of biotinylated probe DNA. The attachment of DNA probes is simple via avidin–biotin interaction on the electrode surface, however, it needs multiple and different chemical reactions to fix the avidin on varied electrode surface, as well as the passivation procedure to avoid the nonspecific physical adsorption (Nimse et al, 2014).…”
Section: Immobilization Of Dna Probes On the Surface Of Electrodesmentioning
confidence: 99%
“…The same strategy has also been used to detect cardiac troponin I (cTnl) biomarker (C. C. Zhang, Sun, et al, 2020). Furthermore, Yesil et al (2016) reported using poly( l ‐glutamic) acid films coated on the pencil graphite electrode surface to anchor avidin for immobilization of biotinylated probe DNA. The attachment of DNA probes is simple via avidin–biotin interaction on the electrode surface, however, it needs multiple and different chemical reactions to fix the avidin on varied electrode surface, as well as the passivation procedure to avoid the nonspecific physical adsorption (Nimse et al, 2014).…”
Section: Immobilization Of Dna Probes On the Surface Of Electrodesmentioning
confidence: 99%
“…Biosensors for detecting the proper antigen or the immunological markers associated with the infections have demonstrated to be an efficient tool for simple and rapid diagnosis in real time and complex samples. Table shows some examples of methods using electrochemical DNA sensors or immunosensors characterized by their low limits of detection.…”
Section: Tropical Diseasesmentioning
confidence: 99%
“…Thiolated ss-DNA probes reproducing the corresponding fragment of the rpoB gene were immobilized onto a gold electrode surface and EIS measurements in the presence of Fe(CN) 6 3À/4À were made to detect and discriminate complementary (T2) and single-base mismatched oligonucleotides (TN) at the 1 nmol L À1 level, on the basis of the comparatively higher charge transfer resistance observed after hybridization with T2. [107] In a similar approach, Yesil et al [109] fabricated an electrochemical DNA biosensor on a pencil graphite electrode (PGE) by avidin-biotin interaction of a biotinylated probe and avidinattached poly(L-glutamic) acid for detection of specific M. tuberculosis DNA sequence. The discrimination between fully complementary hybridization and mismatch hybridization was performed by measurement of the SWV electrochemical reduction current of Meldola's Blue, obtaining a low LOD of 1.3 nmol L À1 .…”
Section: Electrochemical Affinity Biosensors For Detection Of Tubercumentioning
confidence: 99%
“… 10,11 Because of the limitations of label-free electrochemical detection in terms of sensitivity, 12 we have employed a redox DNA hybridization indicator to monitor the current signals from DNA hybridization events. Various redox DNA indicators that are available include ethidium bromide 13 (EtBr), Hoechst 33258, 14 methylene blue, acridine orange, 15 RuHex 3+ , 16 ferrocene, 17 daunomycin, 18 Meldola blue, 19 and Co(phen) 3 3+ , 20 and others have also been documented. Erdem and colleagues 21 reported the first work on the high discrimination potential of MB binding properties, and they found out that MB demonstrated higher affinity toward guanine bases in ssDNA (before DNA hybridization) compared to dsDNA (after DNA hybridization).…”
Section: Introductionmentioning
confidence: 99%